Perkawinan Beda Agama (Tafsir Ayat Ahkam) - ‎ ‎ ‎, Huzaini ‎ ‎ ‎ (Syakhsiyah Jurnal Hukum Keluarga Islam, 2022)
Talking about interfaith marriage is no longer a new phenomenon but has become commonplace in society and even become a trend among celebrities. However, in interfaith marriages, we often encounter questions about whether or not interfaith marriages are legal and the law in Islam, whether the man or woman is Muslim. Life like this is a necessity that has become the nature or instinct of every human being. Therefore, Islam pays considerable attention to this marriage issue, including marriages between people of different religions or interfaith marriages. Religious texts prohibit Muslim marriages with polytheists. In general, apart from the laws in force in Indonesia, religious teachings also become a "barrier" to marriage. So that most of them took the initiative to carry out marriages abroad or in other ways, namely holding marriages according to the religions of both parties. In this case, those who hold a view based on relativism on religious truth and benefit do not make a problem of marriage between a Muslim and a non-Muslim, both male and female.